24‐Dehydrocholesterol reductase promotes the growth of breast cancer stem‐like cells through the Hedgehog pathway. Issue 10 (13th August 2020) - Qiu, Ting; Cao, Jiawei; Chen, Wanzhou; Wang, Jieyi; Wang, Yaqi; Zhao, Lingjie; Liu, Min; He, Licai; Wu, Guang; Li, Hongzhi; Gu, Haihua
Abstract: Cholesterol is a risk factor for breast cancer. However, it is still unclear whether the cholesterol biosynthesis pathway plays any significant role in breast carcinogenesis. 24‐Dehydrocholesterol reductase (DHCR24) is a key enzyme in the cholesterol synthesis pathway. Although DHCR24 is reported to have different functions in different cancers, it is not clear whether DHCR24 is involved in breast cancer. In this study, we found that DHCR24 expression was higher in breast cancer especially in luminal and HER2 positive breast cancer tissues compared with normal breast. Changes in DHCR24 expression altered cellular cholesterol content without affecting the adherent growth of breast cancer cells. However, DHCR24 knockdown reduced whereas DHCR24 overexpression enhanced breast cancer stem‐like cell populations such as mammosphere and aldehyde dehydrogenase positive cell numbers. In addition, DHCR24 overexpression increased the expression of the Hedgehog pathway‐regulated genes. Treating DHCR24 overexpressing breast cancer cell lines with the Hedgehog pathway inhibitor GANT61 blocked DHCR24‐induced mammosphere growth and increased mRNA levels of the Hedgehog regulated genes. Furthermore, expression of a constitutively activated mutant of Smoothened, a key hedgehog signal transducer, rescued the decreases in mammosphere growth and Hedgehog regulated gene expression induced by knockdown of DHCR24. These results indicate that DHCR24 promotes the growth of breast cancer stem‐like cells in part through enhancing the Hedgehog signaling pathway. Our data suggest that cholesterol contribute to breast carcinogenesis by enhancing Hedgehog signaling and cancer stem‐like cell populations. Enzymes including DHCR24 involved in cholesterol biosynthesis should be considered as potential treatment targets for breast cancer. Abstract : Cholesterol is a risk factor for breast cancer. Our study uncovers that 24‐dehydrocholesterol reductase (DHCR24), a key enzyme in the cholesterol synthesis pathway, promotes the growth of cancer stem‐like cell populations by enhancing the Hedgehog signaling pathway in ER+ and HER2+ breast cancer. Our data suggest that cholesterol contribute to breast carcinogenesis by enhancing Hedgehog signaling and cancer stem‐like cell population.